EFEKTIVITAS PELATIHAN MANAGEMEN STRES PADA ASN DI KOTA METRO - Octa Reni Setiawati; Dewi Lutfianawati; Septa Lia Ariska; Randi Mursandi (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT : THE EFFECTIVENESS OF STRESS MANAGEMENT TRAINING FOR ASN IN A METRO CITY This study aims to determine the effectiveness of stress management training in reducing stress levels of ASN in Metro City. Data was collected using the Perceived Stress Scale (PSS). The research design is a one group pretest-posttest design. The research analysis used is quantitative analysis. Quantitative analysis with hypothesis testing using t-test analysis to determine whether there is an effect of stress management training in reducing stress in ASN. The results showed that there were differences in stress among ASN. The conclusion of this study is that there is a significant difference in stress levels in the experimental group after stress management training, or it can be said that there is an effectiveness of stress management training for ASN in Metro City therefore this research can continue to be carried out to reduce stress on ASN. Keywords: ASN, Stress, Stress Management Penelitian ini bertujuan untuk mengetahui efektivitas pelatihan manajemen stres dalam menurunkan tingkat stres ASN kota Metro. Pengumpulan data dilakukan dengan menggunakan skala Perceived Stress Scale (PSS). Rancangan penelitian ini adalah desain one group pretest-posttest. Penelitian ini menggunakan analisis uji t-test untuk mengetahui ada tidaknya pengaruh pelatihan manajemen stres dalam mengurangi stres pada ASN. Hasil penelitian ini yaitu menunjukkan terdapat perbedaan tingkat stres yang signifikan pada ASN setelah dilakukannya pelatihan manejemen stres, atau dapat dikatakan bahwa adanya efektivitas pelatihan manajemen stres pada ASN di kota Metro sehingga pelatihan ini dapat terus dilakukan guna untuk menurunkan stres pada ASN. Kata Kunci: ASN, Stres, Manajemen Stres